Integration of Handheld Guides in Museums: The Case of Lithuania’s Art Museums - Rutkauskaitė Milda (Meno Istorija ir Kritika, 2019)
The most common technological device found in organisations of cultural heritage is a handheld guide. This device can simultaneously perform several functions, and its integration in permanent expositions has significance both for the operation of organisations of cultural heritage and experience of visitors when they visit a museum or a gallery. It should be noted that art museums and galleries encounter a task to present often static and difficult to understand at first sight works of art in an interesting fashion. Therefore, in this study, the main functions of a handheld guide as a technological device as well as its benefits, problems, and application in art museums are analysed.